Comparative phytochemical and antioxidant profile of crude seed powder, aqueous and methanolic seed extracts of Buchholzia coriacea - Godwin C Ugwu; Joseph Effiong Eyo; Jude Ifeanyi Egbuji; Chiemekam Ezechukwu; Keziah Nwamaka Ibemenuga (International Journal of Phytomedicine, 2017)
The increasing discovery of more medicinal plants have triggered increased scientific screening of their bioactivity in order to provide data that will help physicians and patients make wise decision before using them. This study was designed to elucidate comparative phytochemical and antioxidant properties of crude seed powder, aqueous and methanolic seed extracts of Buchholzia coriacea. The results showed that crude seed powder had the highest alkaloid and phenol content of 3.98 ± 0.00% and 0.92 ± 0.00%, while aqueous extract had the least alkaloid and phenol content of 1.00 ± 0.00% and 0.12 ± 0.00% respectively. Methanolic extracts had the highest phytochemical components among the three extracts with flavonoids (12.03 ± 0.0), saponins (1.99 ± 0.01), terpenoids (2.00 ± 0.00), tannin (0.10 ± 0.00) and phytate (2.02 ± 0.01) compositions, while aqueous extracts had the highest hydrogen cyanide (0.30 ± 0.00) and glycoside (0.35 ± 0.00). Antioxidant (DPPH) activities of B. coriacea showed that aqueous extract and crude seed powder had inhibition concentration (IC50) of 4.65 mg/ml while methanolic extract had IC50 of 5.85 mg/ml. The result of the LD50 of the extracts showed the each extracts was well tolerated at a dose of 5000 mg/kg, an indication of high safety profile. The study therefore clearly demonstrated that methanolic extracts of B. coriacea have antioxidant, antihypertensive, hypocholesterolmic and anticarcinogenic properties owing to the presence of high levels of phytochemical components than the aqueous and crude seed powder.